Tumor necrosis factor alpha, interleukin-1 alpha, interleukin-6, and prostaglandin E2 production in murine peritoneal macrophages infected with Ehrlichia risticii. - van Heeckeren, A M (1993)
Ehrlichia risticii is a gram-negative obligate intracellular bacterium which primarily infects macrophages and crypt epithelial cells in the intestinal wall and is the etiologic agent of Potomac horse fever. To understand the pathogenesis of the disease, we tested whether E. risticii induces inflammation-associated products in thioglycolate-induced mouse peritoneal macrophages. Mouse peritoneal macrophages produced larger amounts of interleukin-1 alpha (IL-1 alpha) but lower levels of tumor necrosis factor alpha (TNF-alpha), IL-6, and prostaglandin E2 (PGE2) when exposed to live or killed E. risticii than when exposed to Escherichia coli lipopolysaccharide (LPS). Preincubation of macrophages with live or killed E. risticii suppressed TNF-alpha, IL-6, and PGE2 generation but not IL-1 alpha production in response to LPS. Murine gamma interferon treatment of macrophages did not influence TNF-alpha, IL-1 alpha, IL-6, or PGE2 production regardless of exposure to E. risticii. Intracellular cyclic AMP was significantly greater in E. risticii-infected macrophages than in uninfected macrophages. These results suggest that increased levels of IL-1 alpha but not TNF-alpha or PGE2 production by macrophages may be primarily involved in the pathogenesis of the disease caused by E. risticii. Increased intracellular concentration of cyclic AMP in infected macrophages may be chiefly responsible for the high level of IL-1 alpha and inhibition of TNF-alpha production in response to LPS.